Response of Lupinus bracteolaris seeds to pre-germinative treatments and experimental conditions - Pinto Paim, Luciana; Demari Avrella, Eduarda; Carolina Alves Horlle, Juliana; Sidnei Fior, Claudimar; Lazarotto, Marília; Pich Brunes, André (Revista de Investigación Agraria y Ambiental, 2021)
Contextualization: Lupinus bracteolaris is a heliophite species that vegetates low lands, open slopes and sandstone hills. Knowledge gap: Despite the high rusticity and potential for covering poor soils, there is still no information to assist in the analysis of its seeds. Purpose: To determine pre-germinative treatments, substrate, temperature, luminosity and water intake in the vigor of Lupinus bracteolaris seeds. Methodology: Fruits were collected from 20 matrix plants, then the seeds were processed and submitted to the following tests: pre-germinative methods (six treatments at 25°C); substrates and temperatures (sand and paper at 20, 25 and 30°C); photoblast test (white light, diffuse-green light and continuous dark under 20°C) and the imbibition curve (control and scarification between sandpaper under 20°C). Evaluations: percentage of germination and formed seedlings, germination speed index, average germination time and seedling formation, using a completely randomized design. Results and conclusions: According to the analyzed variables, the results showed superiority for the pre-germinative treatment between sandpapers for 20 seconds. In addition, the substrate paper germibox and the temperature of 20°C were the most suitable during seed germination. The seeds of Lupinus bracteolaris were classified as neutral-photoblastic and without dormancy.